Effects of rock pore sizes on the PVT properties of oil and gas-condensates in shale and tight reservoirs - Arash Kamari; Lei Li; James J. Sheng (Petroleum, 2018)
Shales make up a large proportion of the rocks with extremely low permeability representing many challenges which can be complex in many cases. A careful study of rock and fluid properties (i.e. PVT of shales) of such resources is needed for long-term success, determining reservoirs quality, and increased recovery factor in unique unconventional plays. In this communication, a comprehensive thermodynamic modelling is undertaken in which capillary pressure is coupled with the phase equilibrium equations. To this end, the data associated with both shale oil and gas-condensates of Eagle Ford shale reservoir located in South Texas, U.S., is used. Different properties, including bubble and dew point pressures, capillary pressure, interfacial tension, liquid and gas densities, and liquid and gas viscosities, are predicted observing the effects of rock pore sizes by the thermodynamic modelling performed in this study. The results demonstrate that the thermodynamic model developed in this study is capable of simulating the PVT properties of oil and gas-condensates in shale and tight reservoirs. For a binary mixture 25:75 C1/C6, the bubble point pressure at different reservoir temperature is increased by increasing the pore sizes from 10 to 50 nm. Furthermore, an increase in pore sizes from 10 to 50 nm can increase the dew point pressure for a studied binary mixture 75:25 C1/C6. Keywords: Shale, Pore size, Oil, Gas-condensate, Thermodynamic modelling